Studies on phytoplankton pigments in a tropical coastal lagoon - Nayar, Sasi; Gowda, G (Indian Journal of Fisheries, 2011)
Temporal variations of phytoplankton pigments in relation to nutrients were estimated at monthly intervals in Talapady lagoon, a shallow coastal lagoon near Mangalore on the southwest coast of India (12Â° 47’N, 74Â° 51’E). Chlorophyll a content varied from 1.14 to 16.2 mg nr3, chlorophyll b from 0.15 to 29.38 mg nr3, chlorophyll c from 0.52 to 54.17 mg nr3, carotenoid pigments from 0.11 to 3.62 mg m3 and phaeopigmerits from 3.02 to 30.52 mg nr3. Spatial variations were not significant. Diel variations were studied during monsoon, postmonsoon and premonsoon, but statistically there were no significant variations.